Implementasi Metode Numerik dan Simbolik dengan Python untuk Penentuan Nilai Limit Fungsi - Anita Talia; Angelica Angelica; Agatha Anggraini Tumanggor; Febryanti Hasibuan; Roberto Karlos Sinaga; Ocha Hosea Sigalingging (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study analyzes the utilization of Python as a tool for calculating function limits, with an emphasis on the application of the SymPy and NumPy libraries. The flexibility of Python allows researchers to perform mathematical calculations efficiently, employing both the symbolic approach provided by SymPy and the numerical methods offered by NumPy. SymPy facilitates the management of complex mathematical expressions and produces accurate symbolic results, while NumPy provides speed and efficiency in executing numerical computations. With active community support and regular updates to the libraries, Python proves to be a robust and flexible environment for research in the field of mathematics. Findings from this study indicate that the combination of these two libraries not only enhances the accuracy of limit calculations but also accelerates the research process, making it a relevant choice in both academic and practical contexts..